Air passenger satisfaction and airport service quality / Manoj Kumar and Krishan Kant Meena - Kumar, Manoj; Meena, Krishan Kant (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Airports have always been concerned with increasing business and aviation traffic. People can travel safely through airports, thus in order to increase traffic and growth at the airport, managers at the airport must be aware of what passengers expect from airport services. This study intends to investigate and analyse several aspects of airport service quality connected to the satisfaction and discontent of air travellers in the context of the airport in Rajasthan, India. Primary data were collected from two airports (one international Airport, and 2 domestic airports). Four hundred passengers were included in the study's sample size and were given a standardised questionnaire evaluating the quality of services at airports. Five key aspects of airport service quality were created using exploratory factor analysis to examine the significant factors. Additional confirmatory factor analysis (CFA) was carried out to evaluate the validity and reliability of the identified variable of airport service quality. Analyze the significance of the relationship between the dependent variable (air travellers' pleasure) and the independent variable (airport amenities and services) using structural equation modelling techniques (airport service). The study's results showed the constructs' high internal consistency. The study's findings indicated a significant positive relationship between passenger satisfaction and the quality of airport services. The study revealed how considerably each component of the quality of airport services differs from passenger satisfaction.